An analytical model of harmonic content no-load magnetic fields and Back EMF in axial flux PM machines regarding the iron saturation and winding distribution. Issue 1 (2nd January 2018) - Baghayipour, Mohammadreza; Darabi, Ahmad; Dastfan, Ali
Abstract : Purpose: This paper aims to propose an analytical model for the harmonic content no-load magnetic fields and Back electric motive force (EMF) in double-sided TORUS-type non-slotted axial flux permanent magnet (TORUS-NS AFPM) machines with surface-mounted magnets considering the winding distribution and iron saturation effects. Design/methodology/approach: First, a procedure to calculate the winding distribution with a rectangular cross-section is proposed. The magnetic field distribution and magnetic motive force (MMF) drop due to saturation in iron cores are then exactly extracted in a 2-D analytical model. The consequent influence on air-gap magnetic field and Back EMF are also calculated using a new iterative algorithm. The results are compared with those of the conventional analytical model without saturation, 2-D finite element analysis (FEA) and an experiment on a fabricated prototype machine. Findings: Unlike the conventional method, the new method yields the no-load magnetic field distributions in air-gap and iron cores and Back EMF very exactly such that the results well match to those of the FEA and experiment. Originality/value: Unlike the conventional winding factor, the winding distribution is considered here along the both axial and circumferential directions, which improves the accuracy level of results for non-slotted structures with relatively large air-gaps. The magnetic field distribution and MMF drop-in iron parts are also calculated as the basis for exact recalculation of air-gap magnetic field and Back EMF. Because of small computational burden beside superior accuracy, the proposed model can be treated as an accurate and fast substitute for FEA to be used during the design procedure or for predicting the other performance characteristics of TORUS-NS AFPM machines.